Effects of experimental insoles on body posture, mandibular kinematics and masticatory muscles activity. A pilot study in healthy volunteers. Issue 3 (June 2015) - Marini, Ida; Alessandri Bonetti, Giulio; Bortolotti, Francesco; Bartolucci, Maria Lavinia; Gatto, Maria Rosaria; Michelotti, Ambra
Abstract Background: It has been hypothesized that different plantar sensory inputs could influence the whole body posture and dental occlusion but there is a lack of evidence on this possible association. Objectives: To investigate the effects of experimental insoles redistributing plantar pressure on body posture, mandibular kinematics and electromyographic (EMG) activity of masticatory muscles on healthy subjects. Methods: A pilot study was conducted on 19 healthy volunteers that wore custom-made insoles normalizing the plantar pressure distribution for 2 weeks. Body posture parameters were measured by means of an optoelectronic stereophotogrammetric analysis; mandibular kinematics was analyzed by means of gothic arch tracings; superficial EMG activity of head and neck muscles was performed. Measurements were carried out 10 days before the insertion of the insoles, immediately before the insertion, the day after, 7 and 14 days after, in four different exteroceptive conditions. Results: The outcomes of the present study show that insoles do not modify significantly over time the parameters of body posture, SEMG activity of head and neck muscles and mandibular kinematics. Conclusions: In this pilot study the experimental insoles did not significantly influence the body posture, the mandibular kinematics and the activity of masticatory muscles during a 14-day follow up period.